Internal reforming and mass transport properties of a reaction sintered Ni-YSZ and a novel porous metal support for SOFC applications - McNeeley, Michael Graham (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri High temperature solid oxide fuel cells have the capability of reforming conventional hydrocarbon fuels into hydrogen directly within the fuel cell anode itself. These systems can achieve efficiencies much greater than current electricity generation techniques using the combustion of fuel. The design of a high performing internal reforming SOFC system is extremely challenging because the anode must function as both fuel reformer and electrochemical anode. The risk of carbon formation in the anode structure itself is a serious concern because the reforming environment is coupled to both reforming activity and the electrochemical activity of the anode. Anode materials must be carefully engineered to perform in this environment. SOFC systems are currently limited by their dependence on ceramic cell components. The use of these components prevents rapid thermal cycling of the SOFC systems giving them poor rapid start up and load following capabilities. To help alleviate these issues, SOFCs using a metal support are being developed. Internal reforming metal supported SOFC systems are extremely well suited for both mobile auxiliary power units and stationary backup power systems, due to their enhanced thermal cycling capabilities. Utilizing the unique Separated Anode Experiment at the Colorado School of Mines the internal reforming and mass transport characteristics of a conventional ceramic anode and a porous metal support are evaluated independent of electrochemical operation. This experiment provides analysis of the anode morphology and how it affects species transport through the structure. These results provide insight to the future design efforts for both ceramic and metal supported SOFC system.